Optimalisasi Pemanfaatan Khitosan Sebagai Pengawet Ikan Teri Kering (Spratelloides Gracilis) - Marlinda Marlinda; Rita Hartati (Universitas Teuku Umar, 2020)
This study aimed to determine the optimum concentration of the use of chitosan in dried anchovies to produce maximum preserved dried anchovies. The anchovies used were 300 grams of wet anchovies in each treatment sampel. The sampel is divided into thee parts, namely sampel 1 with the addition of chitosan each of 1%, 2% and 3%. The results showed that the water content were 33,6%, 33,4% and 32,8% respectively. While the microbiological test showed that the use of chitosan 3% in dried anchovies has a TPC (Total Plate Count) value has an average value lower than dried anchovies with the use of chitosan as much as 1% and 2%. The preferred organoleptic test is dried anchovies which uses chitosan as much as 3% in the parameter of color, visual, aroma and taste. The Results of the study concluded that the most optimal use of chitosan as preservative in the production of dried anchovies was 3%.